Genome and gene evolution of seahorse species revealed by the chromosome‐level genome of Hippocampus abdominalis. (7th November 2021) - He, Libin; Long, Xin; Qi, Jianfei; Wang, Zongji; Huang, Zhen; Wu, Shuiqing; Zhang, Xingtan; Luo, Huiyu; Chen, Xinxin; Lin, Jinbo; Yang, Qiuhua; Huang, Shiyu; et al.
Abstract: Seahorses belong to the teleost family Syngnathidae that evolved a distinct body plan and unique male pregnancy compared to other teleosts. As a classic model for studying evolution of viviparity and sexual selection of teleosts, seahorse species still lack a publicly available high‐quality reference genome. Here, we generated the genome assembly of the big‐belly seahorse, Hippocampus abdominalis with long‐read and Hi‐C technologies. We managed to place over 99% of the total length of 444.7 Mb of assembled genome into 21 linkage groups with almost no gaps. We reconstructed a phylogenomic tree with the big‐belly seahorse genome and other representative Syngnathidae and teleost species. We also reconstructed the historical population dynamics of four representative Syngnathidae species. We found the gene families that underwent expansion or contraction in the Syngnathidae ancestor were enriched for immune‐related or ion transporter gene ontology terms. Many of these genes were also reported to show a dynamic expression pattern during the pregnancy stages of H . abdominalis . We also identified putative positively selected genes in the Syngnathidae ancestor or in H . abdominalis, whose mouse mutants are enriched for abnormal craniofacial and limb morphological phenotypes. Overall, our study provides an important genome resource for evolutionary and developmental studies of seahorse species, and candidate genes for future experimental works.